Arab Republic of Egypt : Management and Service Quality in Primary Health Care Facilities in the Alexandria and Menoufia Governorates - World Bank (Washington, DC, 2013)
This report provides an assessment of the performance of public primary facilities in the Alexandria and Menoufia governorates. The performance is evaluated against the standards introduced with the Health Sector Reform Program; analyzes the quality perceptions, health situation, utilization and economic situation of households living in the catchment areas of the facilities; and examines the management processes of different institutions involved in primary care. Despite Egypt's health sector reform efforts, evidence suggests that issues remain in the quality of service and management in both reformed and non-reformed public primary care facilities, including availability of supplies, correct co-payment exemptions for the poor, and consequently, utilization through the population. There is also increasing evidence that the demand-side empowerment of beneficiaries could improve the governance of health care, which would lead to a quality increase and higher utilization of health care. This suggests the need to explore the potential for demand-side mechanisms to improve service delivery and help ensure improvements in individual and population health.